A test battery to investigate back pain in female soccer players - Haag, T. B.; Schneider, A. S.; Beckmann, C. (Sport Sciences for Health, 2016)
Introduction: Back pain (BP) is a concern in youth and adult soccer players. Medical staff should be aware of possible consequences on health status and physical performance of players and, therefore, should screen and/or test for BP. Objective: The purpose of the study was to assess female soccer players with and without BP in a range of tests. Methods: 18 female youth football players (eight with and ten without BP) from a Bavarian Soccer Club were assessed with a test battery consisting of patients` history, physical examination, questionnaire, Y Balance Test (YBT), Swiss Olympic Test (SOT) and maximum isometric strength of the trunk muscles. Results: Participants without any BP showed non-significant better performance in the SOT and the YBT. In the dynamic lateral isometric muscle strength test, patients without BP had a statistically significant (p < 0.05) better result than the other cohort. Conclusion: Our results show that there is a tendency of the cohort without BP for better outcome. Further testing may be needed to evaluate if our test battery is eligible to investigate BP in female soccer players.